2019
DOI: 10.14740/jem581
|View full text |Cite
|
Sign up to set email alerts
|

Food Neophobia in Patients With Phenylketonuria

Abstract: Background: In phenylketonuria (PKU), only a limited range of natural foods, such as fruits, vegetables, oils and sugars, can be consumed without restrictions. The present study aimed to study if food neophobia (i.e. an unwillingness to eat novel food) occurs in patients with PKU and to compare in non-PKU healthy controls and to identify any associated factors. Methods: This cross-sectional case-control study used a convenience sampling strategy to recruit patients diagnosed with PKU and healthy controls match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Sixty-four of the 79 included studies reported at least one patient-important outcome at individual or population level, and they are displayed in Table 1 for study characteristics. Regarding study design, 18 were case series [ 22 , 23 , 33 , 34 , 40 – 42 , 45 , 54 , 55 , 58 , 60 , 70 , 84 – 87 ], 47 cross-sectional studies [ 6 , 7 , 13 – 15 , 17 – 21 , 24 , 26 , 29 , 30 , 35 – 39 , 43 , 46 , 47 , 53 , 56 , 59 , 61 , 62 , 67 , 68 , 71 , 73 , 75 – 77 , 79 – 81 , 88 – 91 ], 13 case reports [ 34 , 44 , 48 , 51 , 63 , 64 , 69 , 74 , 84 , 87 , 92 – 94 ], and two cohort studies [ 57 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty-four of the 79 included studies reported at least one patient-important outcome at individual or population level, and they are displayed in Table 1 for study characteristics. Regarding study design, 18 were case series [ 22 , 23 , 33 , 34 , 40 – 42 , 45 , 54 , 55 , 58 , 60 , 70 , 84 – 87 ], 47 cross-sectional studies [ 6 , 7 , 13 – 15 , 17 – 21 , 24 , 26 , 29 , 30 , 35 – 39 , 43 , 46 , 47 , 53 , 56 , 59 , 61 , 62 , 67 , 68 , 71 , 73 , 75 – 77 , 79 – 81 , 88 – 91 ], 13 case reports [ 34 , 44 , 48 , 51 , 63 , 64 , 69 , 74 , 84 , 87 , 92 – 94 ], and two cohort studies [ 57 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…3 A Osteopenia Silveira et al 2021 [ 71 ] $ Brazil 101 14.0 45.5 Classic (56.4) and mild (43.6) Patients with late diagnosis and patients diagnosed with tetrahydrobiopterin (BH4) deficiency Individual Overweight and obesity Early NR NR NA Included in Fig. 4 A, and B Teruya, 2019 [ 79 , 82 ] Brazil 23 18 39.0 Classic (47.8) and mild (52.2) NA Not included as quantitative data on outcome of interest not provided in paper Patient adherence to clinical recommendations Poor current adherence to Phe-restricted diet; poor current median adherence to Phe-restricted diet Early (65.2%) Phe-restricted diet and special formula Up to 90 days after born Tonon et al 2019 [ 73 ] £ Brazil 25 19.3 52.0 Classic (52.0) and mild (48.0) NR Individual Overweight or obese Early Phe-restricted diet and special formula 52.8** NA Not included as quantitative data on outcome of interest not provided in paper Vieira, 2010 [ 29 ] $ Brazil 5...…”
Section: Resultsmentioning
confidence: 99%
“…Eating disorders : There is increasing evidence of eating disorders, food neophobia, and adverse attitudes towards food in adults with PKU [ 24 , 30 , 31 , 32 ]. Disordered eating refers to abnormal behaviours focused on eating or feeding, but it does not fit the pattern of a specific eating disorder [ 33 ].…”
Section: Nutritional Vulnerability Of Women With Pku In Their Reprodu...mentioning
confidence: 99%
“…The case series and cross-sectional studies sample size ranged from two [21] to 420 patients [44,45]. Patients' ages ranged from a mean of 3.11 [35] to 19.3 [102] years old (Table 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Seven further studies[24, 26,31, 89,91,100,105] were published initially as a thesis followed by a full-text publication[25,27,32,90,92,101, 106]. When information regarding risk of bias or other aspects related to study criteria were unavailable in the methods, we attempted to contact study authors for additional information.Forty of the included studies were conducted inBrazil [18,20,[24][25][26][27][31][32][33]40,42,43,49,50,52,55,59, 60, 62, 63,[65][66][67][68][70][71][72][78][79][80][86][87][88][89][90][91][92][93][94][95]97,[99][100][101][102]105, 106], seven in Argentina[19, 22, 23, 28-30, 34, 44, 45, 57, 58], ve in Chile[35, 36, 38,39,77], three each in Colombia [46,53,...…”
mentioning
confidence: 99%